Potential for medico-biological applications of potassium sodium niobate: A review - Thu M.; Guzzo C.M.; Glaum J.; Kumar Dubey A.; Matinlinna J.P.; Watts D.C.; Amie Luckanagul J. (My University, 2025)
Potassium sodium niobate (KNN) is a versatile lead-free piezoelectric material with a high Curie temperature (Tc) within the range of commercial soft lead zirconate titanate (PZT). KNN-based systems can be modified to have large piezoelectric coefficients competitive with soft PZT (350–700 pC/N), albeit with lower Tc values. In recent years, utilizing its functional characteristics for a broad variety of in vivo and ex vivo medico-biological applications has been the focus of an increasing number of scientific studies. This review aimed to present state-of-the-art insights into piezoelectric KNN-based ceramics, including KNN, lithium (Li)-doped KNN, copper (Cu)-doped KNN and selenium (Se)-doped KNN, and their potential in medico-biological applications. This review described the crystallographic structure and piezoelectric properties of KNN, the manufacturing protocols and structural modification methods to improve functional properties. The sections on medico-biological applications covered topics such as tissue engineering—regeneration of bone, nerve, and cartilage—wound healing, antibacterial action, cancer therapy, drug delivery, and integrated applications with hydrogels and nanoparticles. A brief background on other piezoelectric materials and their potential for medico-biological applications was also provided. Finally, this review identified gaps in the current state-of-the-art for KNN-based ceramics pointing towards pathways for new research areas. © 2025 Elsevier Ltd